On the post-glacial spread of human commensal Arabidopsis thaliana - Cheng-Ruei Lee (Nature Portfolio, 2017)
Population structure of the model plantArabidopsis thaliana is shaped by glacial refugia and recent admixture. Here the authors show that genetically distinct groups of A. thalianahave spread east-west across Europe since the most recent ice age, likely as a result of human activity.